2023
DOI: 10.1145/3585004
|View full text |Cite
|
Sign up to set email alerts
|

Modern Code Reviews—Survey of Literature and Practice

Abstract: Background: Modern Code Review (MCR) is a lightweight alternative to traditional code inspections. While secondary studies on MCR exist; it is unknown whether the research community has targeted themes that practitioners consider important. Objectives: The objectives are to provide an overview of MCR research, analyze the practitioners’ opinions on the importance of MCR research, investigate the alignment between research and practice, and propose futur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 282 publications
0
3
0
Order By: Relevance
“…To ensure that we have enough historical data for our study, we seek large and popular open-source projects with a rich history of pull-based development. For this purpose, we rely on GitHub as a pioneer in supporting pull-based development and the largest open-source ecosystem [20], which has also been the subject of numerous code review studies [21,22]. To identify such projects, we use the number of stars as a proxy for the popularity of the projects [23] and retrieve the list of the top 1,000 most-starred projects.…”
Section: Studied Projectsmentioning
confidence: 99%
“…To ensure that we have enough historical data for our study, we seek large and popular open-source projects with a rich history of pull-based development. For this purpose, we rely on GitHub as a pioneer in supporting pull-based development and the largest open-source ecosystem [20], which has also been the subject of numerous code review studies [21,22]. To identify such projects, we use the number of stars as a proxy for the popularity of the projects [23] and retrieve the list of the top 1,000 most-starred projects.…”
Section: Studied Projectsmentioning
confidence: 99%
“…2 Background and related work Badampudi et al (2023) identified different research themes on code review in a large systematic mapping study where the authors analyzed 244 primary studies until 2021 (inclusive). They further assessed the practitioners' perceptions on the relevance of those code review research themes through a survey of 25 practitioners.…”
Section: Introductionmentioning
confidence: 99%
“…To address this gap, we conduct an exploratory study to assess the feasibility of automatically identifying violation symptoms of architecture erosion from code review comments. The automated identification of violation symptoms could act in a complementary way to modern code review: the latter addresses code changes in general through knowledge sharing (Badampudi et al, 2023), while the former can offer an extra layer of scrutiny. For example, such an automated approach can issue warnings for potential or ignored violation symptoms, preventing the integration of code changes with architectural violations into the code base, and ensuring a more robust and reliable development process.…”
Section: Introductionmentioning
confidence: 99%